2018
DOI: 10.1155/2018/2468105
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Ameliorates Cognitive Deficit and Improves Hippocampal Synaptic Plasticity in Adult Rat with Neonatal Maternal Separation

Abstract: Exposure to adverse early-life events is thought to be the risk factors for the development of psychiatric and altered cognitive function in adulthood. The purpose of this study was to investigate whether electroacupuncture (EA) treatment in young adult rat would improve impaired cognitive function and synaptic plasticity in adult rat with neonatal maternal separation (MS). Wistar rats were randomly divided into four groups: control group, MS group, MS with EA treatment (MS + EA) group, and MS with Sham-EA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…MS induces both functional and structural changes in several brain regions including the PFC, hippocampus, amygdala and nucleus accumbens (150,158163) . More specifically, impaired synaptic long-term potentiation, dendritic atrophy as well as reduced dendritic spine density have been reported in the medial PFC and hippocampus of adolescent and adult MS rats (63,68,97,104,116,140,153,158,164171) . By contrast, MS induces dendritic hypertrophy in the amygdala (57) .…”
Section: The Maternal Separation Modelmentioning
confidence: 95%
“…MS induces both functional and structural changes in several brain regions including the PFC, hippocampus, amygdala and nucleus accumbens (150,158163) . More specifically, impaired synaptic long-term potentiation, dendritic atrophy as well as reduced dendritic spine density have been reported in the medial PFC and hippocampus of adolescent and adult MS rats (63,68,97,104,116,140,153,158,164171) . By contrast, MS induces dendritic hypertrophy in the amygdala (57) .…”
Section: The Maternal Separation Modelmentioning
confidence: 95%
“…In line with the notion that DH is involved in spatial memory, rats that went through MS show a deficit in spatial memory in the Morris Water Maze (MWM) task [100]. Another study using a longer MS protocol (PND 1-20) demonstrated a similar reduction in the dorsal SC-CA1 LTP in vivo and a spatial deficit in the MWM task in adulthood [101]. Accordingly, the LBN model of early life stress also leads to an LTP impairment at the dorsal SC-CA1 synapse during adulthood [102,103].…”
Section: Plasticity In Early Life Stress Models: Diversity Across Thementioning
confidence: 67%
“…Using isoflurane (RWD, Shenzhen, China), the EA rats were positioned in the induction case with an anesthetized concentration of 5% for the initial 5 min for deep anesthetized condition, and then they were moved to the EA operating platform with a 2% concentration for the middle 10 min, decreasing to 1.5% for the last 5 min. Disposable acupuncture needles as previous reported (Guo et al, 2018) were inserted to the acupoints of GV20 and GV29. The Master-8 Stimulator (Master-8, AMPI, Israel) was connected to deliver electrical current to the needles.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as acupuncture or EA can ameliorate depressive-like behaviors, a rat model of depression is a tool that has been widely used to investigate the antidepressant effects of acupuncture (Lu et al, 2016, 2017; Jiang et al, 2017). “Baihui” (GV 20) – “Yintang” (GV 29) are considered to be the optimized acupoint modules for mental illness (Duan et al, 2009a, 2014; Jiang et al, 2017), and our previous study indicates that EA at GV 20–GV 29 acupoints ameliorates cognitive deficits and improves hippocampal synaptic plasticity in adult rats with neonatal MS (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%